2004
DOI: 10.1074/jbc.m401240200
|View full text |Cite
|
Sign up to set email alerts
|

Glyoxalase II of African Trypanosomes Is Trypanothione-dependent

Abstract: The glyoxalase system is a ubiquitous pathway catalyzing the glutathione-dependent detoxication of ketoaldehydes such as methylglyoxal, which is mainly formed as a by-product of glycolysis. The gene encoding a glyoxalase II has been cloned from Trypanosoma brucei, the causative agent of African sleeping sickness. The deduced protein sequence contains the highly conserved metal binding motif THXHXDH but lacks three basic residues shown to fix the glutathione-thioester substrate in the crystal structure of human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
65
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 53 publications
(71 reference statements)
5
65
0
1
Order By: Relevance
“…Although the L. major genome contains a putative GLO2 (LMFLCHR12 92), which is 51% identical to T. brucei GLO2 at the amino acid level (20), we were unable to detect any GLO2 activity in cell extracts of L. major, which may be because of the insensitivity of the assay method or instability of the enzyme. T. brucei GLO2 readily loses activity because of loss of its metal cofactor (20), and thus L. major GLO2 may have lost activity during dialysis to remove trypanothione and glutathione cosubstrates.…”
Section: Discussionmentioning
confidence: 41%
See 3 more Smart Citations
“…Although the L. major genome contains a putative GLO2 (LMFLCHR12 92), which is 51% identical to T. brucei GLO2 at the amino acid level (20), we were unable to detect any GLO2 activity in cell extracts of L. major, which may be because of the insensitivity of the assay method or instability of the enzyme. T. brucei GLO2 readily loses activity because of loss of its metal cofactor (20), and thus L. major GLO2 may have lost activity during dialysis to remove trypanothione and glutathione cosubstrates.…”
Section: Discussionmentioning
confidence: 41%
“…L. major GLO1 thus represents a member of a previously uncharacterized family of GLO1 enzymes. During our investigations into L. major GLO1, an independent study reported that GLO2 from Trypanosoma brucei was highly selective for mono-and bis-S-D-lactoyltrypanothione (20). Taken together, these observations provide compelling evidence for trypanosomatids possessing a unique trypanothione-dependent glyoxalase system.…”
mentioning
confidence: 49%
See 2 more Smart Citations
“…Uniquely, this is dependent upon trypanothione (N 1 ,N 8 -bis(glutathionyl)spermidine or T[SH] 2 ) 2 (4), whereas their human hosts use glutathione ((␥-L-glutamyl-L-cysteinylglycine or GSH). Trypanothione is involved in protective processes, defending against oxidative stress through peroxidase systems (5), against reactive aldehydes through the glyoxalase system (6,7), and against toxic xenobiotics through the trypanothione S-transferase (TST) (8). All these processes depend upon trypanothione being maintained in its dithiol form by trypanothione reductase.…”
mentioning
confidence: 99%